Corrective feedback preferences of primary school and university students - Cubukcu, Feryal; Aksak, Kubra (Revista Arbitrada Interdisciplinaria Koinonía, 2020)
Corrective feedback has attracted more and more attention as it has an important place in language teaching and learning process (Kim, 2004). In this respect, Sheen and Ellis (2011) define corrective feedback as “the feedback that learners receive on the linguistic errors they make in their oral or written production in a second language (L2)” (p. 593). The main aim of this study is to investigate the most and the least corrective feedback types preferred by primary school and university students. The participants of the study determined by the convenience sampling method comprise 50 primary school and 50 university students. Students are required to mark the feedback types they prefer when they make errors. The results indicate that recasts and asking direct questions are the most favored feedback types chosen by students despite the proficiency level gap.